HUBUNGAN KUALITAS HIDUP DENGAN KEJADIAN PENYAKIT JANTUNG KORONER DI RUANG HIGH CARE UNIT (HCU)MURNI TEGUH MEMORIAL HOSPITAL MEDAN - EKA ISRANIL LAILY (LP2MTBM MAKARIOZ, 2021)
Coronary Heart Disease (CHD) is a condition where there is an imbalance between the myocardium's need for oxygen and the supply provided by the coronary arteries. Coronary Heart Disease consists of unstable angina pectoris (UAP) and myocardial infarction (ST elevation myocardial infarction / STEMI and ST elevation myocardial infarction / NSTEMI). The prevalence of CHD in Indonesia continues to increase. In fact, it is now certain that the tendency of the causes of death in Indonesia to shift from infectious diseases to cardiovascular diseases. In 1991, the CHD mortality rate was 16%, then in 2001 the figure jumped to 26.4%. The CHD mortality rate is estimated at 53.5% per 100,000 population in Indonesia. This study aims to determine the relationship between Quality of Life (Physical Health, Psychological Health, Activity Levels, Social Relations, and Environment) with Coronary Heart Disease Incidence in the High Care Unit (HCU) Pure Teguh Room. Memorial Hospital Medan 2017 . Sampling in this study with total sampling with accidental sampling technique. The results of this study indicate that physical health has a significant relationship with the incidence of CHD as many as 36 respondents (72%) with the results of the chi-square test with a 95% confidence level (p = 0.000 < 0.05), 21 respondents (42%) psychological health with chisquare test results (p = 0.005 < 0.05), activity level as many as 24 respondents (48%), with chi-square test results (p = 0.034< 0.05), social relations as many as 24 respondents (48%), with the results of the-square test (p = 0.034 <0.05), the environment as many as 31 respondents (62%), with the results of the -square test (p = 0.000<0.05). Health workers should provide health education, with comprehensive efforts that include preventive, promotive, curative. And rehabilitative. Appropriate efforts to reduce and control the prevalence of CHD and improve people's quality of life.